Keefektifan Steinernema spp. terhadap Spodoptera exigua - F. X. Wagiman; B. Triman; Rr. Siti Astuti (Jurnal Perlindungan Tanaman Indonesia, 2003)
Effectiveness of entomopathogenic nematodes Steinernema spp. against mortality of larvae and pupae of Spodoptera exigua Hubner (Lepidoptera: Noctuidae) was evaluated in the Laboratory of Nematology and Biological Control at the Faculty of Agriculture, Gadjah Mada University. The most virulent isolate of the nematode was selected amongst isolates from Solo, Jombang, and Medan. The effectiveness was determined by analising mortality of the S. exigua that was treated with Steinernema spp. at concentration rates of 0, 50, 100, 200, 400 infective juvenil (IJ) per 1.5 mL aquadest. Inoculation of the nematode was done by filter paper method. Results showed that all isolates were able to infect the third instar of S. exigua. Solo and Jombang isolates caused relative similar in mortalities ca. 98 and 94%, and significantly higher than Medan isolate ca. 86. Hence, the Solo isolate was preferred for efficacy against the insect larvae and pupae. The mortality of S. exigua due to the Steinernema spp. was influenced by the insect instars. The insect mortality-rates of L1, L2, and pupae were 13,3; 6.6 - 13,3; 23,3 - 60% and lower than those of L3, L4, and L5 ca. 41,6 - 75; 46,6 - 60; and 66,6 - 90%, respectively. The nematode concentration-rates did not influenced the mortality of L1, L2, L3, L4, and pupae but it significantly influenced the L5 mortality. The concentration rate of 200 IJ per 1.5 ml aquadest caused the highest mortality.